ANALISIS PENANGANAN HASIL TANGKAPAN NELAYAN YANG DIDARATKAN DI TEMPAT PENDARATAN IKAN BEBA KABUPATEN TAKALAR - Andi Asni; Kasmawati Kasmawati; Ernaningsih Ernaningsih; Mustamin Tajuddin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
The decline in quality and high post-harvest damage are caused by, among others, the way of catching, poor handling methods, the length of the supply chain, the inadequacy of handling facilities. The way fish are handled both on the ship and in the fish landing is directly related to the quality of the fish. This research was carried out for eight months, namely from April to December 2020, at the Beba Fish Landing Site (TPI) in Takalar Regency. The study aims to analyze the quality level of fish and how to handle fish caught by fishermen landed at TPI Beba Takalar. This research was conducted by survey method through direct observation of fish landed by fishermen at TPI Beba Takalar. The types of fish selected are 10 types of fish that are predominantly landed at the study site. The survey was conducted to collect data on fish quality quality by observing the pH parameters and organoleptic properties of fish including eye conditions, gills, odor, and texture. Observations were also made on how fish were handled in TPI. The data analysis carried out is the determination of pH and organoleptic properties. The results showed that the average organoleptic test results in sample fish were values of 7-8, these values showed that the quality of fish freshness was still good. Meanwhile, the results of measuring the average pH of fish 6.5 - 7.0 show that fish still have good freshness quality. The way the fish handling is carried out at the Beba Landing Site still generally uses coarse ice with improper handling methods.